Internal and External Factors on Cost Capital of Apparel and Luxury Goods Companies in Indonesia Stock Exchange - Jerry Marmen Simanjuntak; Adler Haymans Manurung; Nera Marinda Machdar; John EHJ FoEH; Jhonni Sinaga (Universitas Warmadewa, 2025)
This study aims to explore the determinants of the cost of capital for apparel and luxury goods companies listed on the Indonesia Stock Exchange. It utilizes annual data from 2016 to 2023 and employs a panel data model. The findings indicate that both internal and external factors influence the cost of capital. Internal factors include leverage, the interest coverage ratio (ICR), and taxes, while external factors include interest rates and exchange rates.